State level changes in energy intensity and their national implications - Bernstein, Mark (Mark A.) (Rand, 2003)
The National Energy Policy released by the Bush Administration in 2001 calls for continued reductions in U.S. energy intensity, typically defined as energy consumption per dollar of gross economic output. The Department of Energy's Office of Energy Efficiency and Renewable Energy asked RAND to examine changes in energy intensity as part of a larger effort to identify state-level factors that may contribute to efficient energy use nationwide. The authors examined changes in energy intensity from 1977 through 1999 across the 48 contiguous states and in each of the states' residential, commercial, industrial, and transportation energy-consuming sectors. They identified a number of factors that may explain why some states had different patterns of energy intensity than others: energy prices; the mix of industrial and commercial activities; production capacity utilization; capital investment and new construction; population and demographics; climate; technological innovation; and the energy policies of national, state, and local governments. The results from this study suggests that opportunities may exist for the Department of Energy to increase its involvement in helping states to share information and to provide guidance on state-level actions that are effective in reducing energy intensity.